GENETIC GAIN DAN DIFFERENTIAL SELECTION CALON INDUK NILA PUTIH (Oreochromis sp.) JANTI STRAIN SINGAPURA F5 UMUR 5 BULAN YANG DIPELIHARA DI KOLAM AIR DERAS - Yuliana S. Rahayu; Bambang Triyatmo; Murwantoko Murwantoko; Toni Kuswoyo (Jurnal Perikanan Universitas Gadjah Mada, 2013)
The purpose of this research was to observe the genetic gain value of 5 months white tilapia breeders of ﬁ fth generation (F5) Singapore strain (ss) Janti compared with fourth generation (F4) and to revealed the differential selection value of 5 months white tilapia breeders of F5 ss Janti from average weight of top 100 compared to average weight of the population. Research was done for 5 months white tilapia (Oreochromis sp.) breeders of F5 ss Janti. The tilapia cultured in running water system for a month. The research performed for 5 months white tilapia breeders of ss Janti through individual selection method (selective breeding). The white tilapia breeders ss strain used in this research consisted of 400 male and 400 female. The selection of the white tilapia was done randomly. Parameter measured included total weight, length, survival rate, feed amount and water quality for culturing. The result showed that the F5 had increased growth weight of each individual with genetic gain value against the F4 was 30.12 % for the male and 27.92 % for female. The genetic gain value was better than several other selective breeding of tilapia before. The top 100 average weight of the 5 months white tilapia Janti breeders of F5 ss strain (184.03 ± 22.87 g to 224.88 ± 24.31 g) was  higher than average weight of the population (131.27 ± 38.98 g to 163.31 ± 47.17 g). The differential selection value of white tilapia breeders was 37.70 g for male and 40.19 g for female. The weight of male tilapia population was less various than female ones.